2009
DOI: 10.1093/brain/awp141
|View full text |Cite
|
Sign up to set email alerts
|

About the role of visual field defects in pure alexia

Abstract: Pure alexia is an acquired reading disorder characterized by a disproportionate prolongation of reading time as a function of word length. Although the vast majority of cases reported in the literature show a right-sided visual defect, little is known about the contribution of this low-level visual impairment to their reading difficulties. The present study was aimed at investigating this issue by comparing eye movement patterns during text reading in six patients with pure alexia with those of six patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 53 publications
4
59
1
3
Order By: Relevance
“…These visual field defects are not Fig. 1 Visual fields at initial presentation showing slight right homonymous hemianopia causally related to the severity of visual recognition impairment [8]. Furthermore, the visual cortex plays a role in processing color vision.…”
Section: Discussionmentioning
confidence: 96%
“…These visual field defects are not Fig. 1 Visual fields at initial presentation showing slight right homonymous hemianopia causally related to the severity of visual recognition impairment [8]. Furthermore, the visual cortex plays a role in processing color vision.…”
Section: Discussionmentioning
confidence: 96%
“…Studies of patients with pure alexia (Dejerine, 1892;Cohen et al, 2003;Pflugshaupt et al, 2009), and functional brain imaging (Nobre et al, 1994;Jobard et al, 2003;Glezer and Riesenhuber, 2013) have put to light a region in the left ventral occipitotemporal cortex (the visual word form area; VWFA), which is thought to carry out this computation (Cohen et al, 2000). The VWFA then broadcasts orthographic information to language areas involved in central aspects of reading, including stored lexical information (the "deep" reading route), and grapheme-phoneme conversion (the "surface" reading route; Jobard et al, 2003;Price, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This region, called the visual word form area (VWFA) (Cohen et al, 2000(Cohen et al, , 2002McCandliss et al, 2003), is shaped by reading experiences (Hashimoto and Sakai, 2004;Baker et al, 2007;Brem et al, 2010;Dehaene et al, 2010) and is not sensitive to low-level features of written words, such as size, position, font, or letter case (Dehaene et al, 2004;Binder et al, 2006;Vinckier et al, 2007;Glezer et al, 2009;Qiao et al, 2010;Braet et al, 2012). Neuropsychological studies have further revealed that the VWFA is necessary for reading, as the lesion of the VWFA is related to pure alexia with the hallmark feature of word-length effect (Mani et al, 2008;Pflugshaupt et al, 2009;Starrfelt et al, 2009). While extensive studies have focused on how the VWFA is tuned to visual properties of words, little is known about whether top-down influences modulate the VWFA.…”
Section: Introductionmentioning
confidence: 99%